5 - Disciplinary Decadence and the Decolonisation of Knowledge - Gordon, Lewis R. (Africa Development, 2021)
In celebration of the fortieth anniversary of CODESRIA, an institution from the Global South devoted to taking responsibility for the production of social science knowledge, this article explores what it means to pursue such a task under the threat of colonial imposition at methodological and disciplinary levels, which, the author argues, carries dangers of disciplinary decadence marked by the fetishisation of method. The author offers alternatives through what he calls ‘a teleological suspension of disciplinarity, and raises th question not only of the decolonisation of knowledge but also norms.